2019
DOI: 10.3389/fpls.2019.01634
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Promotes Jasmonic Acid Accumulation and Plays a Key Role in Citrus Canker Development

Abstract: Antagonism between jasmonic acid (JA) and salicylic acid (SA) plays pivotal roles in the fine-tuning of plant immunity against pathogen infection. In this study, we compared the phytohormonal responses to Xanthomonas citri subsp. citri (Xcc) between the citrus canker-susceptible (S) cultivar Wanjincheng orange (Citrus sinensis Osbeck) and-resistant (R) cultivar Jindan (Fortunella crassifolia Swingle). Upon Xcc infection, SA and JA were strongly induced in Jindan (R) and Wanjincheng orange (S), respectively, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…To evaluate canker resistance in the CsWRKY22 transgenic plants, leaves of transgenic and WT plants were inoculated with an Xcc suspension by the infiltration method 23 . Ten days after inoculation (dai), CsWRKY22 -overexpressing plants showed much more serious symptoms than WT plants, whereas the opposite trend was observed in RNAi plants (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate canker resistance in the CsWRKY22 transgenic plants, leaves of transgenic and WT plants were inoculated with an Xcc suspension by the infiltration method 23 . Ten days after inoculation (dai), CsWRKY22 -overexpressing plants showed much more serious symptoms than WT plants, whereas the opposite trend was observed in RNAi plants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Healthy 6-month-old leaves from transgenic and WT plants were used to perform in vitro inoculation with our previously described methods 23 . The pathogen Xcc was isolated from naturally infected leaves of sweet orange in an orchard in Yunnan Province, China 11 .…”
Section: Methodsmentioning
confidence: 99%
“…JA regulates plant development in many aspects, including inhibition of seed germination, promoting lateral root formation and inducing root regeneration (Huang et al ., 2017). Interestingly, our group previously showed that ABA cooperated with JA and SA signaling to affect Xcc‐induced pustule formation and the susceptibility to citrus canker in sweet orange (Long et al ., 2019). Together, these data above strongly indicate that CsLOB1 regulates cell division and growth via mediation of hormone signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The plant hormone treatments were performed as described previously (Long et al ., 2019). Fully mature leaves were inoculated with sterile cotton pre‐soaked with 5 ml solution of 10 µ m NAA, 1 µ m ZT, 1 µ m BL, 400 µ m GA or 100 µ m ABA (Sigma, USA), or water.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogen of citrus canker appeared to promote JA accumulation through hijacking host ABA production, which could suppress SA-mediated defenses and benefit pathogen development (Long et al, 2019 ). Consistently, DEGs involved in JA, ET, and ABA signaling were nearly all upregulated in the C Las-infected leaves and barks ( Figure 6 ), and so were those participating in JA biosynthesis, such as allene oxide cyclase 4 ( AOC4 ), lipoxygenase 3 ( LOX3 ), 12-oxophytodienoate reductase 2 ( OPR2 ), and peroxisomal acyl-coenzyme A oxidase 1 ( ACX1 , Supplementary Tables 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%